2011
DOI: 10.1108/00242531111176772
|View full text |Cite
|
Sign up to set email alerts
|

Training cataloguing professionals at the University of the West Indies, St Augustine: part 2

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Cataloguing and classification is a foundation course so, if it is taught only at the postgraduate level only a notable librarian and not a cataloguer will be produced thus Library schools are training half-baked librarians who are fully equipped with the cataloguing and classification skills. (Yacoob and Bowen-Chang (2011). This is why it is important that LIS students must be continually prepared and retrained with the knowledge and the skills of the changing information environment and this must be brought to bear in the delivery of their training programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cataloguing and classification is a foundation course so, if it is taught only at the postgraduate level only a notable librarian and not a cataloguer will be produced thus Library schools are training half-baked librarians who are fully equipped with the cataloguing and classification skills. (Yacoob and Bowen-Chang (2011). This is why it is important that LIS students must be continually prepared and retrained with the knowledge and the skills of the changing information environment and this must be brought to bear in the delivery of their training programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Representatives of companies from which a new system is purchased usually train library personnel in its use. In addition, in some instances, library personnel are oftentimes sent abroad on attachments and other training programs to hone their skills or develop new ones so that the library is always on the cutting edge of new technologies (Hosein and Bowen-Chung, 2011). Moreover, the Department of Library and Information Studies (DLIS) at UWI, which is the only school in the English-speaking Caribbean that educates librarians to the graduate level, is rising to the challenge and is equipping future librarians with the requisite skills needed to function in the digital environment and its courses cover most, if not all, the skills proffered by Gbaje (2012).…”
Section: Underutilization Of Information Technology For User Services: Implications For Academic Libraries In the English-speaking Caribbmentioning
confidence: 99%
“…The priorities of the authors chime significantly, in this instance, with those of Yacoob Hosein and Portia Bowen‐Chang (Hosein and Portia, 2011) of the University of the West Indies who, in their training of cataloguing professionals (to catalogue acquisitions such as the Colin Laird Map collection and the Michael Goldberg collection of postcards) concluded that “training is even more important for specialist cataloguers in today's digital environment with the advent of metadata, RDA standards and various mark‐up languages”, concluding that “the indigenous nature of the materials” produced a training need for original cataloguing, which requires additional levels of bibliographic documentation and research.…”
mentioning
confidence: 96%